Chicken soup for the kid's soul : 101 stories of courage, hope and laughter - Canfield, Jack (Chicken soup, 1998)
Presents stories--including several by celebrities such as Shaquille O'Neal, Shannon Miller, and Kathy Ireland--of inspiration for children on such topics as love, friendship, family, attitude and perspective, and overcoming obstacles.